2020
DOI: 10.1002/jia2.25543
|View full text |Cite
|
Sign up to set email alerts
|

High levels of viral load monitoring and viral suppression under Treat All in Rwanda – a cross‐sectional study

Abstract: IntroductionAiming to reach UNAIDS 90‐90‐90 targets, nearly all sub‐Saharan African countries have expanded antiretroviral therapy (ART) to all people living with HIV (PLWH) (Treat All). Few published data exist on viral load testing and viral suppression under Treat All in this region. We assessed proportions of patients with available viral load test results and who were virally suppressed, as well as factors associated with viral suppression, among PLWH in 10 Rwandan health centres after Treat All implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Overall 46 studies [2,20‐24,26‐30,32,40,43,45,49‐51,53,61,63,65,68,69,72,74‐94] reported on retention on ART or being on ART and 34 (74%) provided clear definitions of numerators and denominators. The majority of studies were longitudinal (29 studies, 63%), 13 were cross‐sectional and four of mixed design.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall 46 studies [2,20‐24,26‐30,32,40,43,45,49‐51,53,61,63,65,68,69,72,74‐94] reported on retention on ART or being on ART and 34 (74%) provided clear definitions of numerators and denominators. The majority of studies were longitudinal (29 studies, 63%), 13 were cross‐sectional and four of mixed design.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 studies reported numbers or percentages of patients retained at this step [8,20‐32,34,36,40‐43,46,56,58,65,68,69,72‐74,76‐93,95‐99]. The majority of studies (32 studies, 62%) covering this step were longitudinal studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations